Histone Modification of Colorectal Cancer by Natural Products - Zijun Geng; Meiqi Chen; Qixuan Yu; Shuoxi Guo; Tianli Chen; Da Liu (Pharmaceuticals, 2023)
Natural products play important roles in the pathogenesis of many human malignancies, including colorectal cancer, and can act as a gene regulator in many cancers. They regulate malignant cell growth through many cellular signal pathways, including Rac family small GTPase 1 (RAC1)/PI3K/AKT (α-serine/threonine-protein kinase), mitogen-activated protein kinase (MAPK), Wnt/β-catenin pathway, transforming growth factor-β (TGF-β), Janus kinase and signal transducer and activator of transcription (JAK-STAT), nuclear factor kappa-B (NF-κB), the Notch pathway, Hippo pathway, and Hedgehog pathway. In this review, we describe the epigenetic roles of several natural products, e.g., platycodin D (PD), ginsenoside Rd, tretinoin, Rutin, curcumin, clove extract, betulinic acid, resveratrol, and curcumin, in colorectal cancer, including their impact on colorectal cancer cell proliferation, apoptosis, invasion, migration, and anti-chemotherapeutic resistance. The aim is to illustrate the epigenetic mechanisms of action of natural products in cancer prevention and treatment, and to provide (1) a theoretical basis for the study of the role of epigenetics in influencing colorectal cancer; (2) new directions for studying the occurrence, development, and prognosis of colorectal cancer; and (3) new targets for treating and preventing colorectal cancer.